Kebijakan Poros Maritim Jokowi dan Sinergitas Strategi Ekonomi dan Keamanan Laut Indonesia - M. Najeri Al Syahrin (Indonesian Perspective, 2018)
As a maritime country Indonesia has economic and security opportunities as a foundation for national development. The future of the Indonesian maritime is realized through the synergy between the economic and the security aspect. This article describes the importance of such synergies within the framework of the global maritime fulcrum. Economic development in this framework is realized through ‘tol laut’ and connectivity of goods and services throughout Indonesia. In terms of security issues, the combating of illegal fishing is a form of defense policy as well as effort to maintain Indonesia’s territorial sovereignty. On one hand, this paper stresses the importance of economic development supported by defense and security stability. On the other hand, the development of defense posture requires a robust economic strength. Economy and security are two aspects that are inseparable and mutually supportive as an effort to realize the ideals of Indonesia as a global maritime fulcrum.Keywords: Global maritime fulcrum, economic and security, ‘tol laut’, illegal fishing